Quantitative investigation of laser ablation based on real‐time temperature variations and OCT images for laser treatment applications. Issue 3 (15th November 2021) - Fan, Yingwei; Ma, Qiong; Li, Mengsha; Luan, Dian; Kang, Hongxiang
Abstract: Background and Objective: Lasers are widely employed in clinical applications. In vivo monitoring of real‐time information about different‐wavelength laser surgeries would provide important surgical feedback for surgeons or clinical therapy instruments. However, the quantitative effect of laser ablation or vaporization still needs to be further explored and investigated. Here, we investigate and quantitatively evaluate the ablation variations and morphological changes of two laser ablation models: point‐ and sweeping‐based models. Methods: An infrared thermal imager was used to monitor the temperature variations, and curve fitting was used to build the relationship between the laser radiation duration/sweeping speed and quantitative parameters of the ablated areas. Optical coherence tomography (OCT) images were used to visualize the inner structure and evaluate the depth of the ablated craters. Optical attenuation coefficients (OACs) were computed to characterize the normal and ablated tissues. Results: The results demonstrated that there was a good linear relationship between radiation duration and temperature variation. Similarly, a linear relationship was observed between the sweeping speed and quantitative parameters of craters or scratches (width and depth). The mean OAC of normal tissues was significantly distinguished from the mean OACs of the ablated craters or scratches. Conclusion: Laser ablation was investigated based on a quantitative parameter analysis, thermal detection, and OCT imaging, and the results successfully demonstrated that there is a linear relationship between the laser parameters and quantitative parameters of the ablated tissues under the current settings. Such technology could be used to provide quantitative solutions for exploring the laser‐tissue biological effect and improve the performance of medical image‐guided laser ablation in the future.